PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI STAF AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD Kota Dumai) - Tengku Asri Yunita; Amries Rusli Tanjung; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of applying government accounting standards, internal control system and the competency of accounting staff to the quality of local government financial reports statement of the regency government of Dumai. Research was conducted at “satuan kerja perangkat daerah”(departements of the reregency government of Dumai). The population in this study is a staff / employees who are involved in the process of preparing financial statements. Sample collection technique using purposive Sampling and the respondents totalled 78 people. The type of data used are primary data. The collection of data by way of a questionnaire. Data were analyzed using multiple linear regression analysis with SPSS version 20.00.The results showed that the application of the accounting standards of governance, internal control system and the competence of accounting staff positive and significant impact on the quality of local government financial reports Kota Dumai. The coefficient of determination shows the effect of the application of the accounting standards of governance, internal control system and the competence of accounting staff positive and significant impact on the quality of local government financial statements amounted to73.4%.Keywords: Accountancy, Control, Competency, and Financial Statement